2018
DOI: 10.1177/1941738118799084
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Exercise-Related Sudden Cardiac Arrest in Young Athletes: Can We Do Better?

Abstract: Public access defibrillator programs should be universal in schools and youth sporting venues and have the potential to increase survival after SCA in young athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 36 publications
2
50
0
3
Order By: Relevance
“…Indeed, survival from SCA is increasing with improved emergency response programmes and access to automated external defibrillators (AED). 14 A better understanding of the epidemiology of SCA/D in young athletes is needed to inform more effective and targeted prevention strategies. The purpose of this study was to determine the aetiology and incidence of SCA/D in USA competitive athletes through a comprehensive, prospective surveillance in collaboration with national centres.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, survival from SCA is increasing with improved emergency response programmes and access to automated external defibrillators (AED). 14 A better understanding of the epidemiology of SCA/D in young athletes is needed to inform more effective and targeted prevention strategies. The purpose of this study was to determine the aetiology and incidence of SCA/D in USA competitive athletes through a comprehensive, prospective surveillance in collaboration with national centres.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding survival after sudden cardiac arrest (SCA), Drezner et al 44 found that non-Hispanic/Latino White athletes had a higher survival rate than athletes from minority groups. This finding was supported by examinations of trends in disparities for pediatric mortality in SCA.…”
Section: Health Equity and Its Significance For Atsmentioning
confidence: 99%
“…El-Assad et al 45 assessed out-of hospital pediatric SCA deaths over 16 years and found that although mortality decreased over time in all racial and ethnic groups, non-Hispanic Blacks/African Americans had the highest mortality rate. Drezner et al 44 noted that this may have been due to minority patients' being less likely to receive bystander cardiopulmonary resuscitation and schools with fewer resources being less likely to have a cardiac response plan and an automated external defibrillator. 44 However, when an AT was present, 83% of athletes survived.…”
Section: Health Equity and Its Significance For Atsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the local high school level in the United States (US), several studies have identified a lack of overall compliance with safety standards related to exertional heat illness (EHI) prevention and treatment such as heat acclimatization and emergency action plans [ 16 , 17 , 18 , 19 , 20 , 21 ]. Conversely, when a policy is in place, it has been shown to be effective in improving patient outcomes following a catastrophic injury [ 22 , 23 , 24 ]. In the US, each state can set forth its own set of policy requirements for local high schools to follow.…”
Section: Introductionmentioning
confidence: 99%